Effectiveness of Plasma Therapy in Patients with COVID-19 Infection – A Retrospective Record-based Descriptive Study - Murali Shankar Bhat; Sripada G. Mehandale; Raghavendra R. Huchchannavar (Acta Medica International)
Introduction: The COVID-19 pandemic presented an unprecedented challenge to the medical community, leading to numerous therapeutic interventions being explored. Convalescent plasma therapy (CPT), derived from recovered COVID-19 patients, was one such treatment used in the absence of proven therapies. However, its efficacy remained a topic of debate. Materials and Methods: This retrospective study aimed to assess the effectiveness of CPT in patients admitted to the intensive care unit (ICU) with moderate-to-severe COVID-19 infection. Data included comorbidities, treatment regimens, partial pressure of oxygen/fraction of inspired oxygen (PaO2/FiO2) ratios, oxygen therapy duration, and outcomes. Patients were divided into groups based on CPT receipt. Statistical analysis was performed to compare the two groups. Results: Out of 72 patients, 36 received CPT, and 36 did not. Patients who received CPT had longer ICU and hospital stays. The mortality rate was higher in the CPT group (50%) compared to the non-CPT group (22.2%). Patients with comorbidities experienced higher mortality rates. Notably, the CPT group exhibited improved PaO2/FiO2 ratios on day 2. Complications related to CPT were minimal. Conclusion: The use of CPT in COVID-19 treatment did not impact overall survival or hospital stay duration.